2016
DOI: 10.1126/scitranslmed.aaf3634
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein binds to TOM20 and inhibits mitochondrial protein import in Parkinson’s disease

Abstract: α-Synuclein accumulation and mitochondrial dysfunction have both been strongly implicated in the pathogenesis of Parkinson’s disease (PD), and the two appear to be related. Mitochondrial dysfunction leads to accumulation and oligomerization of α-synuclein, and increased levels of α-synuclein cause mitochondrial impairment, but the basis for this bidirectional interaction remains obscure. We now report that certain post-translationally modified species of α-synuclein bind with high-affinity to the TOM20 presequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
451
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(481 citation statements)
references
References 47 publications
23
451
2
5
Order By: Relevance
“…demonstrated that mice with global overexpression of human wild type α-syn in the brain using the Thy1 promoter exhibited age dependent accumulation of α-syn in mitochondria in the nigrostriatal dopaminergic pathway, impaired electron transport chain function and enhanced oxidative stress 42 . Recently, Greenamyre’s laboratory reported that specific forms of post-translationally modified α-syn bind with high affinity to the mitochondrial receptor TOM20, resulting in mitochondrial dysfunction and production of reactive oxygen species 45 . From the Zhuang’s group, inducible hA53T-α-syn mice exhibited severe mitochondrial fragmentation that preceded dopaminergic neurodegeneration and other pathologies 19 .…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that mice with global overexpression of human wild type α-syn in the brain using the Thy1 promoter exhibited age dependent accumulation of α-syn in mitochondria in the nigrostriatal dopaminergic pathway, impaired electron transport chain function and enhanced oxidative stress 42 . Recently, Greenamyre’s laboratory reported that specific forms of post-translationally modified α-syn bind with high affinity to the mitochondrial receptor TOM20, resulting in mitochondrial dysfunction and production of reactive oxygen species 45 . From the Zhuang’s group, inducible hA53T-α-syn mice exhibited severe mitochondrial fragmentation that preceded dopaminergic neurodegeneration and other pathologies 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that certain post-translationally-modified forms of α-synuclein – including small, covalent oligomers – can bind to and disrupt the mitochondrial protein import machinery, causing impaired respiration and inducing oxidative stress [33]. Such a pathway highlights the fact that DOPAL-mediated α-synuclein oligomers could both initiate PD mechanisms and result from them.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models of PD, enhanced production of ROS has been observed, with alterations of the antioxidant enzyme levels 144. Mitochondrial dysfunction caused by α-synuclein could be a source of enhanced production of ROS, as has been observed in several experimental models 140,145. Overexpression of wild or mutant α-synuclein in SH-SY5Y cells has also been shown to increase the intracellular level of ROS 146.…”
Section: Parkinson’s Diseasementioning
confidence: 91%